Authentic assessment for affective domain through student participant in community services - Masnida Hussin,; Mohamad Syahmi Said,; Noris Norowi,; Nor Azura Husin,; Mas Rina Mustaffa, (Penerbit Universiti Kebangsaan Malaysia, 2021)
An authentic assessment is expected to have a positive impact on students' learning and motivation. One strategy to provide practical assessment for authentic tasks is by engaging the students to the community where they are familiar and comfortable. The students’ involvement in community services is able to effectively provide vibrant existence information for improving the sense of responsibility among students before they become part of the community. However, evidence from the community services’ activities complicated the assessment process where many documents need to be checked and verified. In our work, we designed an online authentic assessment framework of students’ involvement in the community activities in terms of the affective domain. The affective domain addresses the grasp of attitudes and values that fuels teaching and learning (T&L) processes. Our assessment tool aims to provide a clear assessment guideline to evaluate the students’ ability on analyzing real issues. It also makes the assessment process easier where the evaluation materials can be assembled, previewed, edited and published instantly through online. We hope that the incorporation of student involvement in community services into course assessment shall make the learning process more inspiring.